The short- and long-term effects of life events on residential mobility. (March 2016) - Warner, Cody; Sharp, Gregory
Abstract: In this paper we examine how life events impact inter-neighborhood residential mobility among a cohort of young adults from the United States. We combine choice-based models of mobility with life-course principles to argue that life events associated with the transition to adulthood should be associated with residential mobility in the short-term, but residential stability in the long-term. Unanticipated and disruptive events, on the other hand, are expected to place individuals on a long-term trajectory of residential instability. Longitudinal survey data covering nearly 30 years allows us to capture short-term effects, average effects, and trends across time. We find particularly strong short-term effects on mobility for marriage and homeownership, both of which subsequently lead to long-term stability. We also find that divorce and incarceration (an emerging turning point in the life-course) predict instability in both the short- and long-term. Additional analyses suggest that some events – like homeownership – are immediately stabilizing, while others – like marriage – lead to stability across time. We conclude by discussing the contributions of the findings to our understanding of residential mobility and the transition to adulthood in the contemporary United States.